Indonesian online newspaper editorials on sexual violence: A critical metaphor analysis - IsmayatiHusna Conia; SudanaDadang; GunawanWawan (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Metaphor is an important linguistic device both as a conceptual mapping and as a tool to embed ideology in public discourse such as editorials that consist of many regular expressions. The regular expression is the feature in a corpus application to identify common key terms used in corpus. The regular expression can be described using linguistic device such as metaphor to conceptualize an abstract idea and to embed a certain ideology. There have been few studies which focus on ideology analysis using metaphor. Accordingly, this study aims to look into the regular expression that use metaphors in Indonesian newspaper editorials on sexual violence and investigate the underlying beliefs of the metaphors use. To achieve the purpose of research, Charteris-Black’s Critical Metaphor Analysis and mixed method was employed to analyze the data in this study. Moreover, the data was collected from the leading news platform in Indonesia: Kompas, Tempo, Media Indonesia, and Republika from 2016-2022. Results revealed that Sexual Violence Bill, Sexual Violence Cases, and Sexual Violence Perpetrator were the common regular expressions that employ metaphors in the editorials. The metaphors of a journey were associated with Sexual Violence Bill, the metaphors of a war were associated with Sexual Violence Cases, and the metaphors of a predator were associated with Sexual Violence Perpetrator. These metaphors indicate the use of human rights ideology by as they focus on what a good society is and how to achieve it. Future research including more editorials, particularly those with different backgrounds could be useful to provide a comprehensive account of this subject.